Identification of atrial fibrillation‐associated lncRNAs in atria from patients with rheumatic mitral valve disease. Issue 7 (11th April 2019) - Wu, Jine; Han, Dan; Shi, Rui; Chen, Mingxia; Sun, Jingwen; Tian, Hongyan; Yan, Yang
Abstract: Objective: We analysed lncRNA expression profiles in atrial samples from patients with rheumatic mitral valve disease (RMVD) to identify the potential differences in atrial fibrillation (AF)‐associated lncRNAs between RMVD patients with AF and sinus rhythm (SR). Methods: Masson's trichrome staining and scanning electron microscopy were performed to evaluate the tissue morphology. Western blotting was performed to detect the expression of fibrosis‐related proteins. Difference analysis, Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and gene co‐expression networks were also adopted to perform IncRNA expression profile analysis in atrial samples. Results: Masson's trichrome staining indicated higher contents of fat deposition and fibrous tissue in atrial samples from patients with AF than from patients with SR. Western blotting showed that fibrosis‐related proteins, including smad2, TGFβ1, MMP9, and TIMP1, were upregulated in atrial samples from patients with AF compared to those from patients with SR. lncRNA expression profiles showed different lncRNA expression levels between RMVD patients with AF and SR. Moreover, GO, KEGG and gene co‐expression networks showed consistent results and indicated that differentially expressed genes might contribute to the pathogenesis of AF. Conclusion: Our results revealed the potential roles of IncRNAs in the development of AF in patients with RMVD, and lncRNAs may be responsible for morphological and physiological differences in atria between RMVD patients with AF and SR. Abstract : In this study, we evaluated the differences in the expression of lncRNAs in atrial samples between rheumatic mitral valve disease patients with atrial fibrillation and sinus rhythm. The results showed different expression levels of lncRNAs in atrial samples between these two groups of patients, and different lncRNAs might contribute to the pathogenesis of atrial fibrillation.